P33 HPV16-dependent promoter methylation in HNSCC. Issue 5 (May 2015) - , .; Weiss, D.; Rudack, C.
Abstract : Background: Aberrant promoter methylation of specific genes and infection with Human Papillomavirus 16 (HPV16) are known risk factors for the development of Head and Neck Squamous Cell Carcinoma (HNSCC). In previous studies we were able to show a significantly higher methylation frequency of Cyclin A1 (CCNA1) in tumors arising from the oropharynx (OSCC). Moreover we found an elevated methylation frequency for HPV-positive OSCC compared to HPV-negative OSCC. The protein expression of CCNA1, however, also showed an increased level in HPV-positive OSCC. We therefore aimed to investigate a possible relationship between HPV16-infection of oral mucosa cells and promoter methylation. Methods: Benign human oral HPV-negative keratinocytes, that were negative for CCNA1 methylation and overexpression, were immortalized by infection with HPV16. We analyzed methylation and expression levels of CCNA1 and expression of the methyltransferases DNMT1, DNMT3a and DNMT3b in malignant HPV-positive and benign HPV-negative cells by methylation-specific PCR and mRNA expression analyses. Results: The malignant HPV16-infected cells showed an expression of E6/E7-mRNA and a different rate of growth against controls. Regarding methylation and expression of CCNA1 we found no relevant differences between HPV-positive and HPV-negative cells. Interestingly, there was a significant higher expression level of DNMT1, DNMT3a and DNMT3b after immortalization of benign cells with HPV16. Conclusion: According to this model, HPV16-infection does not seem to influence methylation or expression of CCNA1 directly. We suppose that there are additional mechanisms, which are important for changing the methylation or expression of CCNA1 in HNSCC. But, we could clearly demonstrate a HPV16-dependent influence on the expression of methyltransferase. In further studies we will investigate the distinct connection between the HPV16-oncogenes E6 and E7 and the expression of methyltransferases. By specific inactivation of the oncogenes E6 and E7 with small interfering RNA (siRNA) we want to undo the higher expression levels of the methyltransferases in order to identify the precise relationship.